373 Response to kisspetin as a possible reference for puberty age in heifer. (5th December 2019) - Nogueira, Guilherme D; Paiva, Ana Flavia T; Rodrigues, Tiago; Frizzarini, Waneska; Scaliante, João
Abstract: The objective of this study was to compare the variation of LH concentrations in response to kisspeptin as a way to evaluate the neuroendocrine maturation of Nellore heifers. The hypothesis was that the LH response to kisspeptin increases with age as the number of kisspeptin receptors increase in the CNS. Initially 50 weaned heifers were segregated according to the weaning weight as light (174±1 kg) or heavy (232±2 kg). Both groups received a kisspeptin injection (10μg/kg; IM) monthly from weaning to 16 months, and blood samples were collected 20 minutes after each application. After 16 months of age, heifers were exposed to bulls (25:1) for 60 days and pregnancy was determined 30 days after the end of the breeding season. The LH concentration in response to kisspeptin increased over time (P = 0.001), but there was no difference between light and heavy heifers over the 8-month period (3.62±0.14, 3.34±0.16 ng/ml; P = 0.3853). Similarly, no differences were observed between heifers that became pregnant or not (3.42±0.12, 3.67±0.20 ng/ml; P = 0.3169). Due to the high LH concentrations at 8 months of age (3.06±0.19 ng/ml), another experiment was performed in younger heifers. Fifty newborn Nellore heifers (29±0.3 kg) from the same herd received monthly injections of kisspeptin until weaning. There was also an increase in LH concentrations in response to kisspeptin over time (P = 0.001), but the mean LH concentrations in this experiment (4.05±0.22ng/mL) were considerably greater than those in postweaning heifers. Our interpretation is that genetic differences likely contributed to the different responses to kisspeptin between the two experiments. In order to test this hypothesis, the LH response to kisspeptin will be evaluated in a large number of animals from different herds at weaning to determine the effect of genetic variability on kisspeptin response and possibly to use this phenotype as a marker for age at puberty.